DISTINCTNESS ASSESSMENT ON YARDLONGBEAN (Vigna sesquipedalis (L.) Fruhw.) VARIETIES (Case study for five yard long bean varieties in PVP right application) - Khadijah, Nurdini; Kuswanto, Kuswanto; Damanhuri, Damanhuri (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2012)
The distinctness assessment as one main aspect in DUS test was examined in five yardlongbean varieties that applied for PVP right. The candidates are Brawijaya 1, Brawijaya 3, Brawijaya 4, Bagong 2 and Bagong 3 which belongs to Prof. Kuswanto of Brawijaya University. The test was carried out into two planting seasons (April-June 2011 and September-December 2011). Randomized Block Design used as test design with a total population of 60 plants per variety, divided into three replicates and sample size were 21 plants or plant parts per variety. Six varieties of common knowledge KP1, KP7, Putih Super, Hijau Super, Parade, and Pangeran were chosen as comparison varieties due to their similarity. The observations were recorded on 50 DUS characteristics as listed in the test guideline document of PPU BUSS yardlongbean (PPU/PVT/19/2). Appropriate statistical analysis (cluster analysis, RBD anova and Duncan Multiple Range Test) used to empower the distincness decision. Results shows all candidates have some clear and consistent difference with their similar varieties. Thus, all candidates should pass the distinctness assessment, which confirmed by the results of statistical analysis.